2011
DOI: 10.1093/bja/aer059
|View full text |Cite
|
Sign up to set email alerts
|

Major complications of airway management in the UK: results of the Fourth National Audit Project of the Royal College of Anaesthetists and the Difficult Airway Society. Part 2: intensive care and emergency departments

Abstract: At least one in four major airway events in a hospital are likely to occur in ICU or the ED. The outcome of these events is particularly adverse. Analysis of the cases has identified repeated gaps in care that include: poor identification of at-risk patients, poor or incomplete planning, inadequate provision of skilled staff and equipment to manage these events successfully, delayed recognition of events, and failed rescue due to lack of or failure of interpretation of capnography. The project findings suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
776
6
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 842 publications
(810 citation statements)
references
References 30 publications
13
776
6
15
Order By: Relevance
“…Airway-related complications are both more common in the ICU environment and more likely to result in harm than elsewhere in hospitals [2,3]. Many factors can explain this: airway management in ICU may often be a true emergency, with less preparation time and increased risk of aspiration; ICU trainees (and consultants) are increasingly from nonanaesthetic backgrounds; ICU nurses have less airway management training than anaesthetic nurses or operating department practitioners; airway equipment may be less readily available than in theatre; and airway complications occur more commonly out of hours when senior clinicians are unavailable [4].…”
mentioning
confidence: 99%
“…Airway-related complications are both more common in the ICU environment and more likely to result in harm than elsewhere in hospitals [2,3]. Many factors can explain this: airway management in ICU may often be a true emergency, with less preparation time and increased risk of aspiration; ICU trainees (and consultants) are increasingly from nonanaesthetic backgrounds; ICU nurses have less airway management training than anaesthetic nurses or operating department practitioners; airway equipment may be less readily available than in theatre; and airway complications occur more commonly out of hours when senior clinicians are unavailable [4].…”
mentioning
confidence: 99%
“…For example, in the famous Munich taxi cab experiment, taxi drivers began to drive faster after the installation of antilock braking systems, and contrary to what was intended, this led to a higher accident rate. 13 There is now emerging interest in introducing capnography into other areas of clinical care, including postoperative recovery areas (where many patients are currently cared for in a state of sedation -often without capnography), 14 the intensive care unit, during cardiopulmonary resuscitation, 15 and even for patients who receive large doses of opioids (e.g., via patient-controlled intravenous analgesia or neuraxial administration). 16 How rapidly capnography, or other smart technologies, will be accepted into clinical practice in these areas remains to be seen.…”
mentioning
confidence: 99%
“…Par exemple, dans la fameuse expĂ©rience chez les chauffeurs de taxi de Munich, les chauffeurs de taxi ont commencĂ© Ă  rouler plus vite après l'installation de systèmes antiblocage des freins et, contrairement aux attentes, cela a dĂ©bouchĂ© sur un taux d'accidents plus Ă©levĂ©. 13 On observe maintenant un intĂ©rĂŞt croissant pour l'introduction de la capnographie dans d'autres champs des soins cliniques, y compris dans les salles de rĂ©veil (oĂą l'on observe actuellement de nombreux patients dans un Ă©tat de sĂ©dation, souvent sans capnographie), 14 aux soins intensifs, au cours de la rĂ©animation cardiorespiratoire, 15 et mĂŞme chez des patients recevant de fortes doses de morphiniques (par exemple, en cas d'analgĂ©sie intraveineuse contrĂ´lĂ©e par le patient ou d'administration neuraxiale). 16 Il reste Ă  savoir Ă  quelle vitesse la capnographie ou d'autres technologies intelligentes seront intĂ©grĂ©es aux pratiques cliniques dans ces domaines d'application.…”
unclassified
“…However, we should consider whether we should continue teaching the use of the Macintosh laryngoscope as the first-line tool for intubation, particularly for specialties, such as emergency medicine and intensive care, where intubation is a relatively infrequent event and difficult intubation tends to be associated with worse outcomes. 12 Indeed, several studies have shown that videolaryngoscopy makes intubation easier for both anesthesiologists and non-anesthesiologists 6,9,13 and in patients with both normal and difficult intubation. 14 It has been demonstrated that there is a poor adherence to guidelines by anesthesiologists both in Europe and in North America.…”
mentioning
confidence: 99%
“…There is a significant variation in resources and skill levels of healthcare providers in various countries, institutions, and even departments within institutions, e.g., anesthesia, intensive care, and emergency departments. 12 While a two-to threeday course in Advanced Cardiac Life Support is effective in teaching resuscitation skills to a wide range of healthcare professionals, this is not the case with advanced airway management where certain technical skills require long periods of practice.…”
mentioning
confidence: 99%